Detection of Brucella melitensis Using Real-time PCR and Isolation from Organs of Meat Goat in Thailand - Ramrin, Luckana; Kanitpun, Reka; Ekgatat, Monaya; Lawhavinit, Ongard (Journal of Mahanakorn Veterinary Medicine, 2016)
Brucella melitensis is the most prevalent causative agent of goat brucellosis: one of the most important zoonotic diseases related to the reproductive losses and abortion. Conventional culture method is considered the gold standard for brucellosis diagnosis. However, this method is hazardous, labor-intensive and time-consuming. Therefore, the present study aims to evaluate an efficiency of Real-time PCR diagnosis method: the more convenient and less time consuming method by comparing to culture method. Total 320 samples of liver, spleen, mammary/inguinal lymph node, mandibular lymph node, popliteal lymph node, parotid lymph node, pre-femoral lymph node and pre-scapular lymph node were collected from seropositive and suspicious meat goats. Primer and probe specific for the insertion sequence (IS711) gene of B. melitensis were used. The limit of detection (LoD) of Real-time PCR assay is 2 femtogram (fg) with no cross reactions with other 20 related pathogens. Compared to the gold standard method, Real-time PCR assay contains 92.45% sensitivity, 92.88% specificity and 92.81% accuracy. In conclusion, Real-time PCR assay is sensitivity and specificity method for the rapid and safe detection of brucellosis diagnosis.